The Role of Entrepreneurship Education in Cultivating Entrepreneurial Interest among Students of the Islamic Economics Study Program - Hajrah (Asha Publishing, 2025)
This study aims to determine the role of entrepreneurship education in fostering entrepreneurial interest among students in the Sharia Economics study program, Faculty of Sharia and Islamic Economics, Tomakaka University, Mamuju. It also aims to identify supporting and inhibiting factors in starting a business. This study uses a qualitative research method with data collection through interviews with students who have received entrepreneurship education through entrepreneurship courses. The results show that entrepreneurship education provided through entrepreneurship courses can foster students' entrepreneurial interest. This is indicated by growing self-confidence in students, the ability to think creatively, being more able to face challenges and exploit opportunities, and increasing insight into the business world. Supporting factors in starting a business are interest, motivation, mentality, and talent, as well as external factors such as market opportunities, capital, economic conditions, and family support. Inhibiting factors in starting a business are fear of failure, lack of confidence, lack of capital, lack of mentor guidance, and minimal insight into the world of entrepreneurship.